STRATEGI PEMBERDAYAAN PNS DALAM RANGKA REFORMASI BIROKRASI - Ashari, M.Si, Dr. Edy Topo (Jurnal Borneo Administrator, 2010)
Human resource is especial asset in an organization and it as one of most important element and also very determining in efficacy of organization to reach the target. So also in government sector, human resource ( civil servant / PNS) take hold of important part to  well-held an efficient and effective government. Thereby, the effort to make-up the quality of civil servant is very important to be conducted in a continuously in order to governmental duty as society servant can better ambulatory. The effort that can be conducted to increase quality of civil servant is “the empowerment". Empowering of civil servant intrinsically as a process of the management arrange of exploitation optimazing and potency of civil servant individual, in career construction and make-up the organizational performance. Empowering of civil servant to be conducted as strategic step to increase the effectiveness and efficiency of organization, through a analyse process to competence and organizational management system in a comprehensively. suitable with the empowerment, civil servant be expected can conduct their duty in a professionally, responsibility, honesty and fairness, and also eliminate the negative image of civil servant as closed unemployment.  Keywords : empowerment, human resource, servant civil